Occurrence of Oidiopsis sp. on Chamaelaucium uncinatum in Argentina - Wolcan, Silvia María (2005)
Powdery mildew of Chamaelaucium uncinatum, caused by Oidiopsis sp., is recorded for the first time in Argentina. Although the teleomophic stage was not found, the characteristics of the fungus were similar to those of the anamorph of Leveillula taurica and might be identified as Oidiopsis sicula. Other than Australia, the centre of origin of this host, this is the first country where this disease has been reported. Descriptions of the symptoms and the pathogen are provided.